Subsídios para a proteção dos fragmentos florestais na bacia hidrográfica do rio Poxim - SE - Costa, Cristiano Cunha (2011)
Faced with the degradation of natural resources, the discussions about environmental issues towards the search for sustainability become common. Thus, the study of forest fragments is important regarding the maintenance of biodiversity. This study aimed to propose, systemically, mechanisms that may contribute to the protection of forest remnants located in the hydrographic basin of the Poxim River. Therefore, it was necessary to characterize the forest fragments from the point of view of landscape studies and also to survey the existing riparian vegetation in the hydrographic basin of the Poxim River in accordance with current legislation, to propose actions of vegetation restoration. In order to survey the use and occupation of the Poxim River hydrographic basin, it was used aerial photographs corresponding to the year 2004, UTM zone 24 South Datum SAD-69 projection, with the help of the program ARCGIS 9.2 on display scale of 1:10,000. Similarly, there was a survey of forest fragments of atlantic forest about the size, shape, and connectivity to the vicinity of these fragments, but it was also possible to do a survey of riparian forest in the hydrographic basin of the Poxim River. It was observed that pasture (40.54%) and agricultural crops (15.63%) occupy the largest areas in the hydrographic basin of the Poxim River and those are the main activities that impact the neighboring fragments. Related to the fragments, 92.71% have an average size of 18.58 hectares and circularity index of 0.34. As to connectivity, most of the fragments (26.53%) are over 900 meters away to the nearest forest patch. In the hydrographic basin there is only 01 registered reservation with 198.84 hectares, demonstrating the failure of the Brazilian Forest Code (1965). The riparian forest in the hydrographic basin corresponds to 7.01%, in which less than half of the total (46.22%) is in accordance with the Brazilian Forest Code (1965) which stipulates a minimum of 30 meters width of riparian vegetation. It becomes necessary to adopt public policies aimed at the protection of forest fragments and restoration of permanent preservation areas, forming ecological corridors allied to planning and management of water resources.